PENGARUH KEPEMIMPINAN KONTAK TANI TERHADAP DINAMIKA KELOMPOK TANI DI KECAMATAN NGEMPLAK KABUPATEN BOYOLALI - Heryani Heryani; Totok Mardikanto; Dwiningtyas Padmaningrum (AGRITEXTS: Journal of Agricultural Extension, 2007)
The research is aimed at studying the leadership applied by the farmer's contact in farmer's group in Ngemplak sub-district, its dynamics, and the impact of the leadership farmer's contact toward the dynamics of farmer's group in Ngemplak, Boyolali Regency. The result of the research shows that the leadership of the farmer's contact, in terms of its characteristic, role, and the function of the farmer's contact is considered to be fair good. Farmer's group dynamics through the sociological approach including social strata, member's role, trust, and appreciation is categorized to be good, while the sanction, norm, authority, and press among the members is also good. Farmer's group dynamics through the psycho-social approach including group objectives, structure, work function, education and maintenance, solidarity, condition, pressure, and the affectivity of the group is categorized to be good. The result of the Spearman Rank Correlation test shows that there is a significant correlation between the farmer's contact leadership and the analysis of the farmer's group dynamics through the sociological and psycho-social approach.